2017
DOI: 10.12965/jer.1735068.534
|View full text |Cite
|
Sign up to set email alerts
|

Effects of special exercise programs on functional movement screen scores and injury prevention in preprofessional young football players

Abstract: To increase movement capacity and to reduce injury risk in young soccer players by implementing a special functional exercise program based on functional movement screen (FMS) and correctives. 67 young male athletes 14–19 years of age from a Super League Football Club Academy participated in the study. Functional movement patterns were evaluated with FMS assessment protocol. Deep squat, hurdle step, inline lunge, shoulder mobility, active straight leg raise, trunk stability push-up, and rotatory stability were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 11 publications
(13 reference statements)
0
27
0
2
Order By: Relevance
“…This suggests that besides training some traditional physical attributes, improving young soccer athletes' movements may significantly impact RSA performance. In this regard, Dinc et al [15] recently presented an off-season training program aimed at reducing asymmetrical and dysfunctional movements, assessed with FMS, in young players. The present study included youth elite and sub-elite athletes, highlighting several differences between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that besides training some traditional physical attributes, improving young soccer athletes' movements may significantly impact RSA performance. In this regard, Dinc et al [15] recently presented an off-season training program aimed at reducing asymmetrical and dysfunctional movements, assessed with FMS, in young players. The present study included youth elite and sub-elite athletes, highlighting several differences between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] The inline lunge test evaluates hip and ankle mobility and stability, quadriceps flexibility, and knee stability. [ 15 ] Dinc [ 19 ] reported that the inline lunge score improved by performing upper and lower extremity stretching, trunk muscle training, and functional movement training. The active straight leg raise mainly evaluates the flexibility of the lower extremity and core stability with lower extremity movement.…”
Section: Discussionmentioning
confidence: 99%
“…FMS training consists of no-load exercises, kettle bell training, core board and cable machine exercises. [ 7 , 13 , 14 , 19 , 20 ] According to the recommendation from Song, [ 14 ] fascial release using a foam roller over the gluteus maximus, quadriceps femoris, tensor fasciae latae, hip adductors, hamstring, triceps surae, latissimus dorsi, and back muscles can also help to improve the FMS score. In that study, trunk training (side planks, curl up, trunk stability) were also undertaken in the intervention group.…”
Section: Introductionmentioning
confidence: 99%
“…Entre las pruebas más utilizadas para evaluar la calidad de movimiento en atletas destaca la batería Functional Movement Screen (FMS) de Cook, Burton, Hoogenboom y Voight (2014a; 2014b). Se han encontrado diferentes estudios que utilizan esta batería en fútbol (Chalmers y col., 2018;Dinc, Kilinc, Bulat, Erten, y Bayraktar, 2017;Lisman, Nadelen, Hildebrand, Leppert, y de la Motte, 2018), destacando que las variables que más influyen en los resultados son el historial de lesiones y el sexo del jugador (Chimera, Smith, y Warren, 2015). Tanto es así que se ha utilizado FMS para predecir el riesgo de lesión del LCA sin contacto en jugadoras de fútbol, determinando que aquellas jugadoras que obtienen una puntuación superior a 14 poseen mayor riesgo (Landis, Baker, y Seegmiller, 2018).…”
Section: Introductionunclassified